Anhydrobiosis in yeasts: Psychrotolerant yeasts are highly resistant to dehydration. Issue 5 (5th March 2019) - Khroustalyova, Galina; Giovannitti, Gaia; Severini, Daria; Scherbaka, Rita; Turchetti, Benedetta; Buzzini, Pietro; Rapoport, Alexander
Abstract: Yeast cells are able to transition into a state of anhydrobiosis (temporary reversible suspension of metabolism) under conditions of desiccation. One of the most efficient approaches for understanding the mechanisms underlying resistance to dehydration–rehydration is to identify yeasts, which are stable under such treatments, and compare them with moderately resistant species and strains. In the current study, we investigated the resistance to dehydration–rehydration of six psychrotolerant yeast strains belonging to two species. All studied strains of Solicoccozyma terricola and Naganishia albida were found to be highly resistant to dehydration–rehydration. The viability of S. terricola strains was close to 100%. Such results have not been previously reported in studies of anhydrobiosis in yeasts. The plasma membrane changes, revealed by determining its permeability under various rehydration conditions, were also surprisingly minimal. Thus, the high level of resistance of psychrotolerant yeast strains might be related to the chemical composition and molecular organisation of their plasma membranes. Aside from plasma membrane characteristics, other important factors may also influence the maintenance of yeast cell viability under conditions of dehydration–rehydration.